Newborn girl with coarctation of the aorta and anomalous left coronary artery from pulmonary artery, with retrograde perfusion of left circumflex artery: a case report. Issue 4 (8th October 2019) - Hölscher, Martin; Knirsch, Walter; Dave, Hitendu; Burkhardt, Barbara E U
Abstract: Background: Anomalous left coronary artery from pulmonary artery (ALCAPA) is a rare coronary abnormality. Although it exists usually as an isolated abnormality, ALCAPA has been described with aortic pathologies like coarctation or aortopulmonary window. Case summary: An 18-day-old female was admitted to the paediatric intensive care unit because of a heart murmur and weak femoral pulses. A transthoracic two-dimensional echocardiography was performed and confirmed suspected diagnosis of aortic coarctation. In addition, a total retrograde perfusion of the left circumflex coronary artery (LCX) was found, without visible flow through the ostium of the left coronary artery (LCA) into the aorta. A coronary angiography was performed, showing a single right coronary artery with a normal right posterior descending artery (RPD). Supplied by collaterals from the RPD, the LCX was perfused retrogradely, passing by the lateral wall of the ascending aorta without flowing into it, but into the right pulmonary artery. At 23 days of age, surgery was performed with resection of the aortic coarctation and reimplantation of the LCA into the posterior aortic wall. Discussion: This case demonstrates that coronary artery anomalies like ALCAPA may occur together with other cardiac malformations. Despite concomitant cardiac lesions, careful assessment of the coronary arteries is mandatory, including cardiac catheterization in case of doubt.